Christian Students In The Digital Age: Between Faith, Technology, And Campus Life At IAKN Kupang - Adinda Langkola; Abryani Fallo; Delni Taek; Diance Lopo; Febrianti Nenosaet; Femi Dethan; Vindry Omanda Snae; driana Indra Santi Sole (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to analyze how the attitudes and opinions of IAKN Kupang students regarding the development of digital technology have brought significant changes to student life, including aspects of spirituality, academics, and social relations. This article discusses the dynamics of Christian student life in the digital era, focusing on students at IAKN Kupang. The method used is a qualitative approach through literature review and observation of student life patterns on campus, as well as interviews. The study results indicate that digital technology offers great opportunities for the development of knowledge, service, and faith communication, but it also presents challenges such as social media addiction, reduced direct social interaction, and the influence of digital culture that can weaken spiritual values. Therefore, Christian students are required to have wise digital literacy skills, maintain the integrity of their faith, and utilizing technology responsibly to support both academic and spiritual growth. This article emphasizes that the balance between faith, technology, and campus life is the key for Christian students in facing the challenges of the digital era.